Pola Pengurangan Sampah Dalam Angkutan Suroboyo Bus - Putri Cahya Sufiyah; Martinus Legowo (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Currently, online transportation has started to appear so that the many modes of transportation that exist at some point are able to make the problem of congestion unresolved. Usually traffic jams often occur on the main roads. This phenomenon finally made the Surabaya City Government issue a new policy, namely by providing public transportation services in the form of Suroboyo Bus. The existence of the Suroboyo Bus is also considered to have other positive impacts such as reducing the quantity of waste waste. Based on the illustration above, this study aims to reveal the pattern of waste reduction in the Suroboyo Bus transportation. This study used qualitative research methods. In addition, the data analysis technique in this study uses Miles and Huberman's data analysis. The data used is secondary data. Secondary data can be sourced from literary sources such as journals, articles, theses, books, websites or other supporting sources. The results show that the pattern of waste reduction is formulated through a payment system that uses waste such as bottles and plastic cups.